Concept of Social Justice through the Lenses of Dr. B.R. Ambedkar: An Appraisal - Rina Avinash Pitale Puradkar (International Society of Philosophy and Cosmology, 2022)
This article reflects upon social justice, which is the essence of the Indian Constitution. To protect the social order of the society, it is the duty of the state to promote social justice for equal opportunity and equal rights for social, economic and political development. This paper makes an attempt to explore the concept of social justice through the lenes of Dr. B.R. Ambedkar. Thereafter, it focuses on his struggles and ideas on social justice in the Indian context and it try to explore the relevance of his concept of social justice in the present times.